Expanding the drug discovery space with predicted metabolite–target interactions - Andrea Nuzzo (Nature Portfolio, 2021)
Using computational approaches, Nuzzo et al. identify 983 potential metabolite–human target interactions from the Inflammatory Bowel Disease (IBD) cohort dataset of the Human Microbiome Project 2 (HMP2) and public databases. These predicted interactions can further the understanding of host–microbiome interactions and assist in drug discovery for IBD and other diseases.